An Analysis of The Acceptance and Accuracy of Google Translate’ s Translation of The Song 'Run' By Onerepublic into Bahasa Indonesia - Marudani, Farah Handini; Hasanuddin (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
This research discusses the acceptability of Google Translate's translations in the song 'Run' by OneRepublic. The aim of this study is to determine the acceptability of Google Translate's translations in translating the song 'Run' by OneRepublic, using adaptation translation techniques and communication in analyzing the structural aspects of the translation results. This research is qualitative in nature and employs a case study model with a documentation method. The findings of this research indicate that in translating songs, especially 'Run' by OneRepublic, the structural aspects of the translation align with the Source Language (BSu). However, the translations produced using Google Translate's features still lack acceptability, as they appear rigid and challenging to comprehend